Efficacy of Taxotere, Thalidomide, and Prednisolone in Patients with Hormone-Resistant Metastatic Prostate Cancer - Rezvani, Hamid; Haghighi, Shirin; Ghadyani, Mojtaba; Attarian, Hamid (Urology Journal, 2012)
PURPOSE: To evaluate the efficacy and safety of combination treatment with thalidomide and taxotere in patients with hormone-resistant prostate cancer. MATERIALS AND METHODS: This clinical trial was performed on 16 patients with hormone-resistant prostate cancer. RESULTS: Mean age of the participants was 72.7 ± 5.39 years (range, 65 to 85 years). In 94% of patients who received the drug combination, prostate-specific antigen level decreased more than 50%. The mean time to progression was 15 months and mean survival time was 23 months. This combination therapy had some adverse events. CONCLUSION: Addition of anti-angiogenic agents, such as thalidomide, can improve therapeutic outcome in this group of patients.